Epicardial Fat Tissue Thickness and Omentin in Patients with Atrial Fibrillation - Dural,Ibrahim Etem (2022)
Abstract Background: Although electrical and structural remodeling has been recognized to be important in the pathophysiology of atrial fibrillation, the mechanisms underlying remodeling process are unknown. There has been increasing interest in the involvement of inflammatory molecules and adipokines released from the epicardial fat tissue in the pathophysiology of atrial fibrillation. Objectives: In our study, we aimed to investigate the relationship of atrial fibrillation with increased epicardial adipose tissue, inflammatory molecules released from this tissue and omentin. Methods: Thirty-six patients who were followed up with a diagnosis of permanent AF at the cardiology outpatient clinic 33 individuals without atrial fibrillation (controls) were included in the study. Epicardial adipose tissue thickness of patients was measured by echocardiography. Serum omentin, IL 6, IL 1 beta, TNF alpha and CRP levels were measured. Man-Whitney U test was performed for comparisons and significance was established at 5% (p<0.05). Results: Epicardial adipose tissue thickness was significantly greater in the patient group (6mm [4-5.5]) than controls (4mm [3-5.5]) (p <0.001). No significant difference was found in the concentrations of omentin or inflammatory molecules between the groups. Conclusion: No relationship was found between atrial fibrillation and serum levels or omentin or inflammatory markers. A relationship between epicardial adipose tissue thickness measured by echocardiography and atrial fibrillation was determined.